Copper‐Free Huisgen Cycloaddition for the 14‐3‐3‐Templated Synthesis of Fusicoccin‐Peptide Conjugates. Issue 6 (18th February 2020) - Masuda, Ryoma; Kawasaki, Yuuya; Igawa, Kazunobu; Manabe, Yoshiyuki; Fujii, Hiroshi; Kato, Nobuo; Tomooka, Katsuhiko; Ohkanda, Junko
Abstract: Mid‐sized molecules have emerged as an attractive chemical space and potentially provide a robust basis for the development of synthetic agents to control intracellular protein interactions. However, the limited cell permeability and chemical tractability of such agents remain to be addressed. We envisioned that target‐templated synthesis of such mid‐sized molecules might provide a solution. Here, we exploited a copper‐free Huisgen cycloaddition for template synthesis using a peptide fragment containing a 4, 8‐diazacyclononyne (DACN) moiety and an azide‐containing fusicoccin derivative in the presence or absence of recombinant 14‐3‐3ζ protein in vitro. Time‐course changes in the yield of products demonstrated that the reaction was accelerated in the presence of 14‐3‐3 and one of the regioisomers was generated predominantly, supporting the template effect. Abstract : Templated tactics : A copper‐free Huisgen cycloaddition of an azide‐containing fusicoccin derivative, and a peptide fragment containing a nitrogen‐embedded cyclic alkyne moiety (DACN) in the presence of 14‐3‐3 protein were evaluated. The results demonstrated that the reaction was accelerated in the presence of 14‐3‐3 and generated one of the regioisomers predominantly, supporting the template effect of 14‐3‐3.